Răspuns :
fie x nr 3
atunci nr2 = 3x, si nr1 = 3x-9
3x-9+3x+x=89
7x = 98
x = 14 - nr3
3*14 = 42 - nr2
42 - 9 = 33 - nr1
atunci nr2 = 3x, si nr1 = 3x-9
3x-9+3x+x=89
7x = 98
x = 14 - nr3
3*14 = 42 - nr2
42 - 9 = 33 - nr1
a+b+c=89 \
b=3c \ => a=3c-9
b=9+a \
-----------------/
a, b, c = ?
----------------/
a+b+c=89
3c-9+3c+c=89
3c+3c+c-9=89
7c-9=89
7c=89+9
7c=98
c=98:7
c=14
b=3c
b=3·14
b=42
a=3c-9
a=42-9
a=33
b=3c \ => a=3c-9
b=9+a \
-----------------/
a, b, c = ?
----------------/
a+b+c=89
3c-9+3c+c=89
3c+3c+c-9=89
7c-9=89
7c=89+9
7c=98
c=98:7
c=14
b=3c
b=3·14
b=42
a=3c-9
a=42-9
a=33